Two Integrator Loop Filters: Generation Using NAM Expansion and Review. (10th January 2010) - Soliman, Ahmed M.
Abstract : Systematic synthesis method to generate a family of two integrator loop filters based on nodal admittance matrix (NAM) expansion is given. Eight equivalent circuits are obtained; six of them are new. Each of the generated circuits uses two grounded capacitors and employs two current conveyors (CCII) or two inverting current conveyors (ICCII) or a combination of both. The NAM expansion is also used to generate eight equivalent grounded passive elements two integrator loop filters using differential voltage current conveyor (DVCC); six of them are new. Changing the input port of excitation, two new families of eight unity gain lowpass filter circuits each using two CCII or ICCII or combination of both or two DVCC are obtained.